2011
DOI: 10.1002/jso.22104
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy in hepatocellular carcinoma and cirrhosis: Evaluation of radiological and pathological response

Abstract: SBRT achieves total or partial radiological response in 37% of patients and total or partial pathological response in 37% of patients with early HCC in the setting of cirrhosis. SBRT may be a safe and effective alternative for local tumor control in patients with HCC and cirrhosis awaiting OLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 58 publications
2
47
0
1
Order By: Relevance
“…SBRT may help reduce this: following SBRT used as a bridging therapy, 63-100% of patients are reported to proceed to transplant, with low rates of toxicity, and with complete and partial pathological responses reported in 14-29% and 23-64% of lesions respectively [39][40][41][42][43] . Mohamed et al recently compared SBRT, TACE, RFA and yttrium-90 microspheres as bridge to transplant therapies in a retrospective series of 60 patients 43 .…”
Section: Sbrt As a Bridge To Transplantmentioning
confidence: 99%
“…SBRT may help reduce this: following SBRT used as a bridging therapy, 63-100% of patients are reported to proceed to transplant, with low rates of toxicity, and with complete and partial pathological responses reported in 14-29% and 23-64% of lesions respectively [39][40][41][42][43] . Mohamed et al recently compared SBRT, TACE, RFA and yttrium-90 microspheres as bridge to transplant therapies in a retrospective series of 60 patients 43 .…”
Section: Sbrt As a Bridge To Transplantmentioning
confidence: 99%
“…[18][19][20][21][22] Other publications apply recommended EASL or mRECIST criteria. [23][24][25][26][27] A single article compared the RECIST and EASL criteria in this indication. Price et al reported in 2012 on a series of 26 patients treated for 29 CHC by SBRT by comparing the morphological evolution according to the RECIST and EASL criteria 16 ( Table 1).…”
Section: Evaluation Of Response After Sbrt For Primary Hepatic Tumorsmentioning
confidence: 99%
“…Facciuto et al [82] provided excellent clinicopathologic correlation among 39 lesions in 27 patients receiving SBRT as bridge therapy prior to OLT. Patients received 24-36 Gy divided in two to four fractions using Novalis-based radiosurgery with image guidance and fiducial marker placement.…”
Section: Recent Experience With Sbrt For Plcmentioning
confidence: 99%